Collaborative and partnership options for promoting health information literacy in rural communities: exploring the challenges - Benson , Oyemike Victor; Obichere , Charlie; Orisakwe , Kingsley (Communicate: Journal of Library and Information Science, 2024)
The paper focuses on challenges of collaborative and partnership approaches in promoting health information literacy in developing countries. The role of library and information professions in collaboration with health workers and allied agencies were articulated. Justification for health information literacy in rural communities, rationale for collaborative and partnership initiatives in promoting health information literacy in rural communities and sustainable partnership options available to library and information professional in the promotion of health literacy were well articulated. The challenges identified include low level of partnership drive among librarians, language differences, poor understanding of information therapy services, poor perception of collaborative initiatives, low level of technological drive, and lack of subject/language experts in packaging health information. Strategies for sustainable collaboration and partnership include intensive lobbying and advocacy, proper orientation and sensitization towards collaborative initiatives, professional commitment towards safe health initiatives, recruitment of skilled personnel in health information management, formulation strong collaborative and partnership policy, establishment of centres for health information literacy, lobbying government and donor agencies for fund/support.